2012
DOI: 10.1002/chem.201200881
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Control of the Supramolecular Chirality of Porphyrin J‐Aggregates

Abstract: The aggregation of achiral sulfonatophenyl- and phenyl-meso-substituted diprotonated porphyrins to chiral J-aggregates is a hierarchical noncovalent polymerization process preceded by a critical nucleation stage. This allows significant enantiomeric excesses by the formation of a few primary nuclei and the control of their growth by the effect that flows (imperfect mixing) have on the secondary nucleation of the J-aggregate particles. In addition, the results strongly suggest that when only one species of aggr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 38 publications
7
30
0
Order By: Relevance
“…During the primary nucleation process, significant enantiomeric excesses can be obtained from the formation of a few primary nuclei, and the vortex stirring controlled the secondary nucleation by assisting the growth of the primary chiral nuclei. 304 This mechanism can be demonstrated from the difference between the CD spectra measured under vigorous shaking and magnetic stirring ( Figure 104B). Thereby, chiral assemblies can be obtained from achiral building blocks.…”
Section: Controlling Handedness Of Supramolecular Chiralitymentioning
confidence: 92%
“…During the primary nucleation process, significant enantiomeric excesses can be obtained from the formation of a few primary nuclei, and the vortex stirring controlled the secondary nucleation by assisting the growth of the primary chiral nuclei. 304 This mechanism can be demonstrated from the difference between the CD spectra measured under vigorous shaking and magnetic stirring ( Figure 104B). Thereby, chiral assemblies can be obtained from achiral building blocks.…”
Section: Controlling Handedness Of Supramolecular Chiralitymentioning
confidence: 92%
“… 46 A reasonable explanation is that under strong shaking a high number of chiral primary nuclei was formed, thus favoring a racemic situation, whereas, vortex-stirring favored the formation of a low number of nuclei most likely evolving to an enantioenriched mixture. 41 , 46 Note that the latter is similar to the crystallization of achiral salts, like NaClO 3 , which under stirring can form scalemic mixtures of enantiopure crystals ( e.g. Kondepudi crystallization scenario).…”
Section: Methods To Reach Non-dissipative Non-equilibrium States (#2mentioning
confidence: 99%
“…the case of the formation of chiral porphyrin aggregates upon symmetry breaking induced by rotary evaporation (Sorrenti et al, 2012), and has been ascribed to a distortion from the planarity of the macrocycles due to steric hindrance. Similar results have been reported by Micali and Monsù Scolaro (Micali et al, 2006), for the case of chiral fractal structures of a water-soluble tetrakis(p-sulphonatophenyl)porphyrin derivative, group, and this event would likely constitute the driving force for the evolution toward the final Type-II species.…”
Section: Spectroscopic Investigationsmentioning
confidence: 99%
“…In the former case, the stereochemical course of the self-assembling process is governed by the presence of chiral groups linked on the porphyrin peripheral frame (Oliveira-González et al, 2015;van der Weegen et al, 2017). In the latter issue, final chiral suprastructures are obtained by interaction of achiral substrates with external physical effectors, such as hydrodynamic directional forces (Sorrenti et al, 2012;Arteaga et al, 2016); magnetic fields (Micali et al, 2012); LB and LS techniques (Chen et al, 2011), or chiral molecular templates, such as surfactants (El-Hachemi et al, 2008), chiral polymeric matrices (D'Urso et al, 2012), chiral ligands (Borovkov and Inoue, 2006;Berova et al, 2007) or carboxylic acids (Castriciano et al, 2011). With this regard, Monsù Scolaro showed that the assembly of a non-chiral porphyrin derivative templated by the two different enantiomers of tartaric acid proceeds with different kinetics and results in final chiral suprastructures with highly different anisotropy factors, which are strictly dependent on the enantiomer used as a templating agent (Castriciano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%